Inferring a weighted elastic network from partial unfolding with coarse-grained simulations - Mendonca, Matheus R. de; Rizzi, Leandro G.; Contessoto, Vinicius [UNESP]; Leite, Vitor Barbanti Pereira [UNESP]; Alves, Nelson A. (Wiley-Blackwell, 2014)
A number of studies have demonstrated that simple elastic network models can reproduce experimental B-factors, providing insights into the structure-function properties of proteins. Here, we report a study on how to improve an elastic network model and explore its performance by predicting the experimental B-factors. Elastic network models are built on the experimental C coordinates, and they only take the pairs of C atoms within a given cutoff distance r(c) into account. These models describe the interactions by elastic springs with the same force constant. We have developed a method based on numerical simulations with a simple coarse-grained force field, to attribute weights to these spring constants. This method considers the time that two C atoms remain connected in the network during partial unfolding, establishing a means of measuring the strength of each link. We examined two different coarse-grained force fields and explored the computation of these weights by unfolding the native structures. Proteins 2014; 82:119-129. (c) 2013 Wiley Periodicals, Inc.
Keywords: normal mode analysis; GNM; pfGNM; WCN; B-factor; vibrational dynamics